PENAMPILAN FISIOLOGI DAN HASIL RUMPUT BENGGALA (Panicum maximum Jacq.) PADA TANAH SALIN AKIBAT PEMBERIAN PUPUK KANDANG, GYPSUM DAN SUMBER NITROGEN - E. D. Purbajanti; R. D. Soetrisno; E. Hanudin; S. P.S. Budhi (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2010)
[PHYSIOLGICAL PERFORMANCES AND YIELD OF GUINEA GRASS (Panicum maximum Jacq.) AS AFFECTED BY APPLICATIONS OF GYPSUM, MANURE, AND NITROGEN]. Agricultural production on saline soil is often hampered by the inherent soil properties that limit the plant to gain optimal growth and development. Objective of this study was to determine the effects of gypsum, manure, and nitrogen applications  on the physiological characteristics and yield of guinea grass. A factorial experiment was set up in a greenhouse, involving two levels of manure (0 and 20 ton ha-1), four levels of gypsum (0, 0.75, 1.5, and 3 ton ha-1), and three levels of nitrogen (0, 50 kg N ha-1 in form of nitrate, and 50 kg N ha-1 in form of ammonium). Application of manure at 20 ton ha-1 produced higher leaf area per plant (LAPP), photosynthetic rate, nitrogen uptake, relative growth rate (RGR), plant height, and forage and dry matter productions as compared to no manure. Similarly, LAPP, photosynthetic rate, and net assimilation rate (NAR) had increased linearly as the gypsum applications were increased from 0.75 to 3 ton ha-1. ANR were increased in quadratic fashion on both manure treatments in accordance with the increment of gypsum applications. LAPP, NAR, ANR, N uptake, plant height, RGR, and dry matter production were increased by application of either nitrate or ammonium application, whereas the highest forage production was found on combination of manure at 20 ton ha-1 and N at 50 kg ha-1 in form of ammonium.